Spontaneously hypertensive rat neuroanatomy: applications to pharmacological research - Amenta, Francesco; Tayebati, Seyed Khosrow; Tomassoni, Daniele (Italian Journal of Anatomy and Embryology, 2010)
Spontaneously hypertensive rats (SHR), which are normotensive at birth and develop sustained hypertension between 3 and 6 months of age, are the model most extensively investigated for evaluating hypertensive brain damage and its treatment. The time-dependent rise of arterial blood pressure and the occurrence of brain atrophy, loss of nerve cells and glial reaction are shared to some extent with what occurs human hypertensive brain. SHR, therefore, can represent a reasonable model of hypertension-related brain damage. Our main studies on cerebrovascular and brain microanatomical changes occurring in SHR and their sensitivity to pharmacological interventions are summarized.